USING BIOPOEM TECHNIQUE TO IMPROVE THE RECOUNT TEXT WRITING SKILL OF THE TENTH GRADERS OF SMA NEGERI 1 MAGELANG IN THE SCHOOL YEAR 2015/2016 - Leni Zulaechah; Sukarno Sukarno; M. Malik Al Firdaus (Faculty of Education and Teachers Training, 2018)
Writing is considered important for the high school students. However, the X MIA 6 Peminatan students of SMA Negeri 1 Magelang still find difficulty in writing the recount text. There are two objectives of the study in this research. The first is to know whether the use of Biopoem technique can increase the recount text writing learning motivation of the tenth graders of SMA Negeri 1 Magelang in the school year 2015/2016. The second is to know how great the improvement of the recount text writing skill of the tenth graders of SMA Negeri 1 Magelang in the school year 2015/2016 who are taught using Biopoem is. The writer conducted a classroom action research.To collect the data, the writer uses non-test (observation, questionnaire, documentation) technique and test technique. The data are analyzed using qualitative and quantitative data analysis technique. Based on the writer’s observation and questionnaire, it shows that there are some changes in the students’ learning motivation after the writer taught using Biopoem technique. There are also improvement of the test mean scores. Based on the description above, the writer concludes that the use of Biopoem technique can increase the students’ recount text writing learning motivation and there is a significant improvement of the recount text writing skill after they were taught using Biopoem technique.